Adapting evidence-based eating disorder treatments for novel populations and settings : a practical guide - Tortolani, Christina C.; Goldschmidt, Andrea B.; Le Grange, Daniel (New York, NY : Routledge, 2021)
"This comprehensive text provides practical approaches to adapting empirically supported treatments for eating disorders for clinicians working with patients of diverse backgrounds and presentations, or within non-traditional treatment settings across levels of care. The book describes empirically and clinically informed treatment adaptations that impact delivery of real-world services for eating disorder patients and generate interest in testing adapted treatments in randomized controlled trials. Featuring contributions from researchers and clinicians with expertise in developing, delivering, and testing interventions for eating disorders, each chapter focuses on a specific population, setting, or training approach. Practical applications are then illustrated through case examples and wisdom gleaned through the contributors' own clinical studies and experiences. Readers working with eating disorder patients of diverse backgrounds and presentations, or within non-traditional treatment settings across levels of care, will gain the necessary skills to support their patients on the journey to recovery and self-acceptance"--
OCLC-licensed vendor bibliographic record.
Keywords: Eating disorders -- Treatment; Evidence-based medicine; PSYCHOLOGY / Psychopathology / Eating Disorders